Trisula Scout School Extracurricular Website Development - Matahari, Tombak; Harditya, Arya; Bhakti, Muhammad Agni Catur; Wandy, Wandy (Journal of Community Services: Sustainability and Empowerment, 2021)
Most schools from all levels in Indonesia already have a website, both public and private schools. Website is a useful formal communication medium for schools to enrich the use of social media. Domain names for schools in Indonesia have also been provided with the.sch.id for easier accessibility and identification. SD Negeri Rambutan 03 Jakarta have a scout extracurricular activity named Trisula, during Covid-19 Pandemic situation, scout weekly activities were shifting from originally face-to-face to an online exercise. This momentum was one of the reasons why the scout website needs to be built. This community service was a qualitative method with an interview approach, discussion and literature review during the pre-development and web-development process. The website has been successfully generated, customized, and implemented using WordPress and has been internally launched last November of 2020